(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2025)
Increasing longevity has become a serious economic, social, and healthcare challenge. Spain is one of the world’s most aging countries. This is frequently linked to circumstances in which individuals experience increased loneliness. Older adults are particularly exposed to events that often entail enormous changes in their relationships, making them more vulnerable to unwanted loneliness. Other risk factors include female sex, age, employment status, educational level, economic status, location, the death of a partner, and deteriorating health. In older adults, a comprehensive geriatric assessment that includes clinical, functional, mental, and social aspects is essential to develop an interdisciplinary strategy for intervention, treatment, and long-term follow-up. There are strategies to reduce unwanted loneliness in this population, which must be implemented by administrative structures and be part of global health strategies.